Estimated frailty prevalence among Israeli elderly - results from a cross sectional national survey - Assaf Buch; Lital Keinan-Boker; Yitshal Berner; Eli Carmeli; Rebecca Goldsmith; Naftali Stern (BMC, 2018)
Abstract Background Increasing longevity presents new social and medical challenges in developed countries. The prevalence of frailty is of interest because of its association with health prognosis and outcomes, but so far there is no single best diagnostic tool for this entity. Therefore, estimated prevalence of frailty in countries varies considerably and ranges between 5% and 58%. In Israel, the nation-wide prevalence of frailty in the elderly population is presently unknown. The objective of our study was to assess the rate of the frailty in elderly Israelis. Methods A post-hoc analysis based on the results of a national Health and Nutrition Survey in Israeli elderly (MABAT Zahav). A non-direct model to estimate frailty was based on five components that were most similar to the common frailty assessment suggested by Morley et al. The frailty state was then reclassified according to different explanatory variables. Results Data collected from 1619 subjects (F/M = 52.9/47.1%) with an average age of 74.6 years were analyzed. Estimated frailty prevalence in the elderly population was 4.9%. Frail people were more likely to have a lower income, be unemployed and have a lower education level. Frailty rates were higher in women, in Jews and in subjects more prone to low physical function. Conclusions The estimated frailty prevalence in the Israeli elderly population, while relatively low, is comparable to some of the rates suggested in the literature. The factors associated with frailty in the Israeli population are in accordance with the existing literature. The suggested model may be helpful in identifying frailty in Israeli elderly.